Study of effect of intravenous iron sucrose on different haematological parameters in patients of anaemia in pregnancy - Chaudhari, Shilpa N.; Ashtekar, Archana; Bamne, Shubhangi; Singh, Manika; Warty, Tanvi; Sharma, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of this study was to evaluate the efficacy of intravenous Iron sucrose by comparing the various hematological parameters before and after infusion of intravenous iron sucrose and also the safety and compliance in cases of pregnancy with anaemia. Methods: One fifty patients visited in OPD with haemoglobin level <7 gm/dl during 1st and 2nd trimester of pregnancy and all patients of 3rd trimester with mild, moderate or severe anemia after satisfying the inclusion criteria were included. These patients were investigated with different hematological parameters. Patient’s hemoglobin, serum iron, total iron binding capacity, peripheral blood smear repeated after the completion of doses after 21 days. Results: Results were significant with increase in haemoglobin from baseline 6.7 ± 1.2 to 10.2 ± 1.9 after 21 days of treatment. There was significant rise of serum iron levels (93.14 ± 1.9 mcg/dl) post treatment. However repeat TIBC (94.66%) significantly decreased from baseline, mean TIBC was 314.66 ± 1.8 mcg/dl. Significant increase was also noted in MCV, MCH and PCV. Conclusions: This study showed significant improvement of hemoglobin and iron stores in pregnant women given calculated dose of iron sucrose complex infusion. It was safe for mother and fetus and is well tolerated.